Alternations in neural oscillation related to attention network reveal influence of indoor toluene on cognition at low concentration. (19th July 2022) - Guo, Dandan; Zhan, Changqing; Liu, Jie; Wang, Zukun; Cui, Mingrui; Zhang, Xin; Su, Xiao; Pan, Liping; Deng, Meili; Zhao, Lei; Liu, Junjie; Song, Yijun
Abstract: Despite accumulative literature reporting negative impacts of high‐concentration toluene, cognitive effects of toluene at low concentration are still unclear. Twenty‐two healthy college students were exposed in a closed environmental chamber to investigate the influence of indoor toluene on cognitive performance and brain activity. During each toluene exposure condition (0 ppb, 17.5 ppb, 35 ppb, and 70 ppb), attention network test and electroencephalogram (EEG) recording were synchronously performed after 4‐hour toluene exposure. Characteristic neural oscillation patterns in three attention networks were compared between four groups. The statistical analyses indicated that short‐term exposure to toluene had no significant impact on behavioral performance of attention network. However, there was a significant increase in the power of theta and alpha band of executive network and orienting network in the whole brain, especially in frontal region when exposed to toluene. Besides, no significant difference was observed in alerting network. The alternations in neural oscillation demonstrated that more effort was required to accomplish the same tasks when exposed to toluene. The present study revealed that short‐term exposure to toluene affected brain activity of attention network even at low concentration, which provided a theoretical basis for the development of safer evaluation methods and standards in the future.